(BEDT‐TTF)2Cu2(HCOO)5: An Organic–Inorganic Hybrid Conducting Magnet. Issue 3 (31st May 2017) - Zhang, Bin; Zhang, Yan; Wang, Zheming; Gao, Zengqiang; Yang, Deliang; Wang, Dongwei; Guo, Yanjun; Zhu, Daoben
Abstract: This month's cover picture results from Professor Bin Zhang's collaborative work between Chinese Academy of Sciences and Peking University (China). Since the discovery of high‐temperature superconductors for hole doping on parent antiferromagnetic compound La2 CuO4, the antiferromagnetic molecular crystal with a (4, 4) grid copper‐formate framework Cu(HCOO)2 (H2 O)4 and its deuterated compound (Cu(DCOO)2 (D2 O)4 ) have been studied extensively for supposed dual‐functional molecular crystals. The cover picture shows the ideal situation by replacing intercalated H2 O with an organic donor. The organic–inorganic hybrid (BEDT‐TTF)2 Cu2 (HCOO)5 is obtained through the electrochemical oxidation of neutral BEDT‐TTF in the presence of an ammonium salt of the 1D copper‐formate framework [(C2 H5 )3 NH]2 Cu2 (HCOO)5 in a C6 H5 Cl‐C2 H5 OH solution. For more details, read the full text of the Communication at 10.1002/open.201700041 . Abstract : "The window to find antiferromagnetic (4, 4) grids, from inorganic dual‐functional materials to molecular crystals with long‐range magnetic ordering and semiconducting behaviour, has been opened. The ultimate goal of our research is to find out new molecular superconductors from antiferromagnetic (4, 4) grid metal‐organic frameworks…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding article at10.1002/open.201700041 .